Crescimento, desenvolvimento e produtividade de cana-deaçúcar em cultivo de cana-planta e cana-soca de um ano Santa Maria, RS - Hanauer, Joana Graciela (2011)
The objectives of this Dissertation were to estimate the base temperature of leaf appearance, determine the phyllochron, leaf area, tillering, leaves number on stem elongation and determine the crop yield of three clones of sugarcane in crops plant and ratooning of one year. A field experiment was conducted during the years 2008 at 2010 at the experimental area of the Crop Science Department, Universidade Federal de Santa Maria, Santa Maria, RS. Three sugarcane clones were used: IAC 822045 (early), SP 711406 (medium) and CB 4176 (late). Experimental design was a complete randomizes block with four replications. Green leaf area was calculated from leaflet length and width. Base temperature (Tb) was estimated using the Mean Square Error (MSE) approach of the regression between accumulated leaf number (LN) and accumulated thermal time (TT). The phyllochron (°C day leaf-1) based on expanded and tip leaf number was estimating using 10°C as base temperature. Phyllochron was calculated as the inverse of the slope of the linear regression between NF and TT. We obtained nonlinear models of power type for the cumulative leaf area (AF) and NF stem. The productivity was determined used the four stems in the growing season of 2008/2009 and eight stems in the growing season 2009/2010. The phyllochron varies during the development sugarcane cycle, with a break point on 15 leaves and increasing following PHYLearly<PHYLentire<PHYLlate. The phyllochron in crops plant is less than phyllochron ratooning of one year to the first 15 leaves. The phyllochron based on expanded leaves number in general was greater than that based on tip leaves number, especially for the first 15 leaves. The power model is appropriate to characterize the allometric relationship between the evolution of green accumulated leaf area from the accumulated number of leaves on main stem. The medium clone (SP 711406) which had slower tillering and constant during its development cycle and has thicker stem and larger leaf area had a greater productivity in the ratooning of one year. The tip number leaves ranges from 14 to 18 leaves at the elongation stem. A variation in the production of green biomass of stem is more affected by the genetic trait of clones than by changes on environment.